Strength and reliability of WC-Co cemented carbides: Understanding microstructural effects on the basis of R-curve behavior and fractography. (February 2018) - Tarragó, J.M.; Coureaux, D.; Torres, Y.; Jiménez-Piqué, E.; Schneider, L.; Fair, J.; Llanes, L.
Abstract: Strength and reliability of WC-Co cemented carbides (hardmetals) are dependent on effective fracture toughness as well as on nature, size and distribution of processing flaws. Regarding toughness, they exhibit a crack growth resistance (R-curve) behavior, derived from the development of a multiligament bridging zone at the crack wake. Accordingly, successful implementation of fracture mechanics requires consideration of tangency criterion, between applied stress intensity factor and R-curve, in addition to fractographic inspection. It is the aim of this study to evaluate the strength behavior of a series of experimental WC-Co grades on the basis of R-curve failure criteria. Results indicate that microstructural effects on the strength of hardmetals may be satisfactorily rationalized following the referred criterion. The analysis includes consideration of nature and distribution of fracture origins, found to be more diverse and wider, respectively, for the harder fine-grained grades. This experimental evidence, together with the fact that these hardmetals exhibit steeper rising R-curves than tougher coarse-grained ones, leads to lower reliability for the former. This investigation documents and validates the great relevance of R-curve behavior for optimizing the mechanical performance of WC-Co cemented carbides on the basis of microstructural design. Highlights: LEFM framework is valid to describe fracture behavior of low-toughness hardmetals. Medium and high-toughness hardmetals require the consideration of R-curve behavior. Low-toughness grades tend to exhibit medium strength levels and low reliabilities. Medium-toughness hardmetals tend to exhibit large strength and reliability levels. High-toughness grades tend to exhibit low strengths levels but high reliabilities.